0432 Insomnia is Associated with Endothelial Dysfunction in Young Adulthood: the Penn State Child Cohort. (25th May 2022) - Fernandez-Mendoza, Julio; Gao, Zhaohui; Calhoun, Susan; Brandt, Kristen; He, Fan; Liao, Jason; Vgontzas, Alexandros; Liao, Duanping; Bixler, Edward
Abstract: Introduction: Clinical and population-based studies in middle-aged and older adults have shown that insomnia is associated with prevalent and incident cardiovascular diseases. However, there is a lack of studies demonstrating an association between insomnia and subclinical cardiovascular measures such as endothelial function in young adults from the general population. Methods: We studied 200 subjects from the Penn State Child Cohort (20-30 years old, 47% male, 22% racial/ethnic minority), who underwent a thorough clinical history and physical examination to ascertain the presence of sleep disorders and body mass index (BMI), in-lab polysomnography to ascertain the apnea/hypopnea index (AHI), and Doppler ultrasound to assess flow-mediated dilation (FMD). We identified the presence of moderate-to-severe difficulties initiating and/or maintaining sleep (i.e., poor sleep) and of insomnia, the latter including a physician diagnosis of the disorder. The study outcome was FMD as a continuous measure and the square root of FMD (sqrt-FMD) to test the robustness of the analysis. General linear models adjusted for sex, age, race/ethnicity, BMI, AHI, alcohol intake, and sleep medication use. Results: Compared to normal sleepers (0.111±0.003), subjects with poor sleep (0.104±0.006) and insomnia (0.092±0.008) showed a significant association with lower FMD levels (p-linear<0.05), with subjects with insomnia having significantly lower FMD levels (p=0.029). Results remained significant and in the same direction based on sqrt-FMD (p-linear=0.015). Conclusion: These data indicate that insomnia is associated with increased risk for cardiovascular disease as early as young adulthood, and independent of major contributors such as obesity, sleep apnea or alcohol use. These data further reinforce the need to include insomnia as a target in the preventative efforts for cardiovascular disease. Support (If Any): National Institutes of Health (R01HL136587, UL1TR000127)